2014
DOI: 10.1111/ctr.12455
|View full text |Cite
|
Sign up to set email alerts
|

De novo use of generic tacrolimus in liver transplantation – a single center experience with one‐yr follow‐up

Abstract: Adoport is safe and effective compared to Prograf when used de novo in LT patients. Tacrolimus costs were significantly reduced by the use of Adoport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
(12 reference statements)
1
14
0
Order By: Relevance
“…Graft loss was reported in two of the de novo studies after KT: in eight patients (15.7%) versus six patients (12.5 %) after generic and innovator Tac, respectively , and the Spartacus trial revealed 0% graft loss versus 2.6% (one patient) with generic and innovator Tac after KT, respectively . Furthermore, there were 2 (4.3%) versus no graft losses reported with de novo innovator Tac after LT . More drug level variability and dose adjustments necessary during the first weeks after transplantation in de novo use and also after conversion was reported .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Graft loss was reported in two of the de novo studies after KT: in eight patients (15.7%) versus six patients (12.5 %) after generic and innovator Tac, respectively , and the Spartacus trial revealed 0% graft loss versus 2.6% (one patient) with generic and innovator Tac after KT, respectively . Furthermore, there were 2 (4.3%) versus no graft losses reported with de novo innovator Tac after LT . More drug level variability and dose adjustments necessary during the first weeks after transplantation in de novo use and also after conversion was reported .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies including 365 patients after LT (191 de novo, 174 conversion) and nine studies including 883 patients after KT (735 de novo, and 148 conversion) compared BPAR of patients on generic Tac with those on innovator Tac after LT or KT, all of them in a parallel design (Table ). However, only two of those studies were randomized controlled trials and a further two were non‐randomized prospective studies . Risk ratios for BPAR rates of patients on generic Tac versus innovator Tac were compared in a forest plot stratified visually by organ and study design (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data are in line with the results of Dannhorn et al who demonstrated a significant reduction of costs with generic TAC by Sandoz in kidney-transplant recipients. 10 Rosenborg et al also found that the conversion from Prograf ® to TAC Sandoz ® after kidney transplantation brought savings, despite costs for extra monitoring. 7 …”
Section: Discussionmentioning
confidence: 99%